Targeting Transcriptional Regulators Affecting Acarbose Biosynthesis in Actinoplanes sp. SE50/110 Using CRISPRi Silencing - Saskia Dymek; Lucas Jacob; Alfred Pühler; Jörn Kalinowski (Microorganisms)
Acarbose, a pseudo-tetrasaccharide produced by Actinoplanes sp. SE50/110, is an α-glucosidase inhibitor and is used as a medication to treat type 2 diabetes. While the biosynthesis of acarbose has been elucidated, little is known about its regulation. Gene silencing using CRISPRi allows for the identification of potential regulators influencing acarbose formation. For this purpose, two types of CRISPRi vectors were established for application in Actinoplanes sp. SE50/110. The pCRISPomyces2i vector allows for reversible silencing, while the integrative pSETT4i vector provides a rapid screening approach for many targets due to its shorter conjugation time into Actinoplanes sp. These vectors were validated by silencing the known acarbose biosynthesis genes acbB and acbV, as well as their regulator, CadC. The reduction in product formation and the diminished relative transcript abundance of the respective genes served as evidence of successful silencing. The vectors were used to create a CRISPRi-based strain library, silencing 50 transcriptional regulators, to investigate their potential influence in acarbose biosynthesis. These transcriptional regulatory genes were selected from previous experiments involving protein–DNA interaction studies or due to their expression profiles. Eleven genes affecting the yield of acarbose were identified. The CRISPRi-mediated knockdown of seven of these genes significantly reduced acarbose biosynthesis, whereas the knockdown of four genes enhanced acarbose production.